Independent Education - As a Process of Professional Training of Students (Journal of Pedagogical Inventions and Practices, 2023)
Today, at the modern stage of development of the educational system, modeling is of great importance. As a result of fundamental changes in educational paradigms, new requirements for modeling innovative didactic systems are emerging.